1983
DOI: 10.1007/bf02463436
|View full text |Cite
|
Sign up to set email alerts
|

Submarine debris flow deposits detected by long-range side-scan sonar 1,000-kilometers from source

Abstract: Debris flow deposits of large aerial extent have been detected on the lower continental rise off northwest Africa using GLORIA long-range dual sidescan sonar.A preliminary interpretation of the sonographs with high-resolution (3.5 kHz) seismic profiles and gravity cores illustrates the potential for spatial mapping of these deposits. The transport directions indicated on the sonographs show that these sediments, emplaced by mass transport, are the downslope continuation of the Saharan Sediment Slide. The dista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

1988
1988
2001
2001

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(11 citation statements)
references
References 12 publications
1
10
0
Order By: Relevance
“…The structureless internal character has been attributed to the scattering of incident sound energy by chaotic bedding and flow structures, while impedance contrasts at the top and bottom of the flows return distinct echoes or reflections (Simm & Kidd 1984). In unconsolidated sediments even a short displacement will be enough to disrupt the continuity of internal reflectors (Embley 1980).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The structureless internal character has been attributed to the scattering of incident sound energy by chaotic bedding and flow structures, while impedance contrasts at the top and bottom of the flows return distinct echoes or reflections (Simm & Kidd 1984). In unconsolidated sediments even a short displacement will be enough to disrupt the continuity of internal reflectors (Embley 1980).…”
Section: Discussionmentioning
confidence: 99%
“…Where lobes coalesce, the resulting overlapping or amalgamated sequence may total a thickness of 50-60 m (Prior & Coleman 1984). On the continental margins off NW Africa (Embley 1976;Jacobi 1976;Simm & Kidd 1984;Kidd et al 1987), eastern N America (Embley 1980), Israel (Almagor & Wiseman 1982), S Korea (Chough 1984) and California (Thornton 1984) debris flows extend down the slope into deep water rise and abyssal plain settings, and range from 1 -6 0 m thick and from several kilometres to several hundred kilometres in length.…”
Section: Discussionmentioning
confidence: 99%
“…Slide scars show erosion to a depth of 80 m and the total area affected was 18000km 2 • Masson et al Cl992b) showed that part of the area mapped by Embley and later workers (e.g. Simm and Kidd 1984;Kidd et al 1985Kidd et al , 1987 as the Saharan Slide in fact belonged to another !arge slide which they termed the Canary Debris Flow. This debris flow is associated with an eroded area of 6000 km 2 on the lower slopes of the westernmost Canary Islands of La Palma and Hierro.…”
Section: Debris Flows On the Continental Marginmentioning
confidence: 97%
“…A large leveed channel appears to be the principal feature within the system . Simm & Kidd (1984) suggested that the debrite identified in the study area is related to the 'Saharan Sediment Slide', which has been described by Embley (1975Embley ( , 1976Embley ( , 1980Embley ( , 1982. On the abyssal plain to the west, channels and debrites are absent, and the basin floor is largely featureless, except for prominent seamounts protruding through the sediment cover and bioturbation structures at the sediment surface .…”
Section: Geological Settingmentioning
confidence: 66%